2023
DOI: 10.2169/internalmedicine.0370-22
|View full text |Cite
|
Sign up to set email alerts
|

Early Esophageal Adenocarcinoma with Non-Barrett's Columnar Epithelium Origin: Two Case Reports and a Literature Review

Abstract: We herein report two cases of early esophageal adenocarcinoma derived from non-Barrett's columnar epithelium. Both patients, a 65-year-old woman and 60-year-old man, had elevated lesions on white-light imaging. Magnifying endoscopy revealed slightly irregular surface and vessel patterns, and both patients were successfully treated with endoscopic submucosal dissection. Histopathologically, both lesions comprised of welldifferentiated gastric mucin phenotype adenocarcinoma. One lesion was accompanied by ectopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Several case reports of EAC derived from ectopic gastric mucosa have been reported (17)(18)(19)(20)(21)(22)(23). Kitasaki et al (17) reported a case of repeated local recurrence at the same site despite multiple radical endoscopic resections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several case reports of EAC derived from ectopic gastric mucosa have been reported (17)(18)(19)(20)(21)(22)(23). Kitasaki et al (17) reported a case of repeated local recurrence at the same site despite multiple radical endoscopic resections.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that EAC in the cervical or upper thoracic esophagus, rich in lymphatic chains and vascular networks, may be difficult to treat and have a poor prognosis (23). The basic treatment strategy for EAC is local control through resection, and some reports have shown that endoscopic resection can be expected to treat cervical esophageal lesions in early-stage cancers (19)(20)(21)(22). Tanaka et al (22) reported a case in which complete resection was achieved with larynx-preserving surgery, indicating that larynx-preserving surgery is possible for localized lesions that do not extend to the hypopharynx as long as negative margins are ensured.…”
Section: Discussionmentioning
confidence: 99%